Phase transition and high-pressure behavior of ulexite, a potential aggregate in radiation-shielding concretes. (12th July 2021) - Comboni, Davide; Pagliaro, Francesco; Gatta, G. Diego; Lotti, Paolo; Battiston, Tommaso; Merlini, Marco; Hanfland, Michael
Graphical abstract: Highlights: Ulexite undergoes a phase transition between 6.6 and 7.1 GPa. The structure of ulexite-II has been solved. A dramatic anisotropic compressional scheme has been found. The P- stability range of ulexite exceeds the working conditions of aggregates in concretes. Abstract: The high-pressure behavior of ulexite [ideally NaCaB5 O6 (OH)6 ·5(H2 O)], a B-bearing raw material (with B2 O3 ≈ 43 wt%) and a potential B-rich aggregate, has been studied by in-situ single-crystal synchrotron X-ray diffraction up to 9.5 GPa, in order to explore its stability field at high pressure, the anisotropy of its compressional behavior and the deformation mechanisms at the atomic scale. Ulexite undergoes a first-order iso -symmetric phase transition, reconstructive in character, between 6.44 and 7.13 GPa (to the ulexite-II polymorph); the crystal structure of ulexite-II was successfully solved and refined. For the low- P polymorph of ulexite (stable in all the working conditions as aggregate in concretes), the isothermal bulk modulus here obtained is K V0 = 36.9(5) GPa, with a strongly anisotropic compressional pattern (finite-Eulerian principal components of the unit-strain ellipsoid: ε1 :ε2 :ε3 ∼7:3:1). Ulexite-II also shows a marked anisotropic compressional pattern and with a resulting bulk softening ( K V0 = 26(4) GPa).